Correlations between the levels of vitamin D, parathormone, calcium, blood phosphates in patients with chronic disease of the kidneys untreated with replacement renal therapy - Aleksey Vladimirovich Smirnov; Mikhail Mikhaylovich Volkov; Ol'ga Vladimirovna Galkina; Aleksandr Anatol'evich Zhloba; Vladimir Leonidovich Emanuel'; A V Smirnov; M M Volkov; O V Galkina; A A Zhloba; V L Emanel (Terapevtic̆eskii arhiv, 2009)
Aim. To characterize correlations between the levels of vitamin D, parathormone, calcium, blood phosphates in patients with different stages of chronic disease of the kidney (CDK) given no therapy replacing renal function (TRRF). Material and methods. Serum levels of creatinine, electrolytes, parathormone (PTH), 25(OH)-vitamin D (calcidiol -CD), 1,25 (OH)2-vitamin D (calcitriol -CT), calcium (Ca) and phosphates (P) excretion with urine were studied in 465 patients aged 52.2 ± 15.5 years with CDK stage I-V given no TRRF having mean glomerular filtration rate (GFR) 51.8 ± 27.1 ml/min. Results. A CT level lowered with CDK progression and directly correlated with GFR, blood levels of Ca and CD. Correlation with PTH was not found. CD did not correlate with GFR. PTH rose from stage II CDK and its concentration in the blood correlated negatively with GFR, blood Ca (in lesser degree), directly correlated with P. Ca lowered at stage V of CDK, P - at stage II, increased at stage IV. In reduction of GFR 24-h excretions of P and Ca diminished in spite of growth of their excreted fractions and were related directly with CT. Conclusion. A rise of PTH and fall of CT occur at early CDK stages. P disbolism seems to play a key role in genesis of hyperparathyrosis. We are the first to show lowering of 24-hour Ca and P excretioin with CDK progression which may be caused by a progressive CT deficiency.